ANALISIS SIFAT KIMIA TANAH PADA LAHAN PERTANIAN DI KELURAHAN KAWANGU KECAMATAN PANDAWAI KABUPATEN SUMBA TIMUR - Umbu Andira; Yonce; Suryani (Jurnal Agro Indragiri, 2022)
Kawangu Village is one of the areas in Pandawai District which has a large agricultural land. However, until now there is no information about the state of soil chemistry on agricultural land. Knowledge of soil chemical properties will provide important information in the context of managing an agricultural land. This study aims to analyze the chemical properties of soil on agricultural land in Kawangu Village, Pandawai District, East Sumba Regency, East Nusa Tenggara Province. This research was carried out in May-June 2022 at Kawangu Village. The research was conducted by survey method and sampling and the samples were analyzed in order to obtain the results of the analysis. The chemical properties observed were available N, available P, available K, cation exchange capacity (CEC), and base saturation (BS). The results showed that the content of N elements ranged from 0.11-0.66% (low to high status), P elements ranged from 15.58-57.78 ppm (low to high status) and P elements ranged from 15.58-57.78 m.e./100g (moderate to Very high status). The condition of the soil CEC ranged from 34.56-39.65 m.e./100g and the soil KB ranged from 72.72-95.71%.Kawangu Village, soil chemical properties